New multifunctional 3D porous metal–organic framework with selective gas adsorption, efficient chemical fixation of CO2 and dye adsorption. Issue 22 (13th May 2019) - Cheng, Shan; Wu, Yunlong; Jin, Jing; Liu, Jiao; Wu, Dan; Yang, Guoping; Wang, Yao-Yu
Abstract : A new porous Mn(ii )-based MOF was obtained. The studies indicated it exhibits an effective storage capacity for CO2, highly efficient catalyst behavior for epoxides with different substituents and rapid adsorption behavior of different dyes. Abstract : A new three-dimensional (3D) porous Mn(ii )-based metal–organic framework [Mn4 (L)2 (H2 O)4 ] n ·4DMF·H2 O (1 ) has been synthesized using Mn(ii ) and the rigid 2, 6-di(2′, 5′-dicarboxylphenyl)pyridine (H4 L) ligand under solvothermal conditions. Structural analysis revealed that MOF1 is an open framework with exposed active nitrogen atoms and rectangular-shaped channels along the b axis (with effective aperture sizes of 11.3 × 8.8 Å 2 and 10.7 × 8.7 Å 2 ). Gas sorption behaviors showed that MOF1 has a relatively high capacity and selectivity for CO2 over CH4 . Thus, the CO2 cycloadditions were studied using different epoxides, displaying the high efficiency of the catalyst. It was also found that MOF1 shows rapid adsorption for the organic dyes. Therefore, MOF1 should be explored as a multifunctional porous material for gas separation, catalysis and dye adsorption.